Regulasi Emosi dan Harga Diri sebagai Faktor Psikologis Penentu Ketahanan Ibu dalam Pemberian Air Susu Ibu Eksklusif pada Ibu Tidak Bekerja - Hotimah, Hananik; Fajar, Nur Alam; Sunarsih, Elvi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
Breast milk is the best source of nutrition for babies, especially during the first six months of life. One important aspect of successful breastfeeding that is often overlooked is the mother's psychological well-being, especially emotional regulation and self-esteem. The purpose of this study was to obtain information on emotional regulation and self-esteem as psychological factors that influence maternal resilience in exclusive breastfeeding in non-working mothers. This study was a narrative literature review from four databases, namely BMC Pregnancy and Childbirth, BMC Public Health, Google Scholar and Google Scholar Indonesia until November 6, 2025. The keywords used for the BMC database were "emotional regulation" AND "self-esteem" AND "exclusive breastfeeding" AND "non-working mother"; for Google Scholar were "maternal" AND "emotional regulation" AND "self-esteem" AND "resilience" AND "exclusive breastfeeding" AND "non-working mother"; for Google Scholar Indonesia were "regulasi ibu" AND "emosi" AND "harga diri" AND "ketahanan" AND "pemberian ASI eksklusif" AND "ibu yang tidak bekerja". A total of 15 articles met the criteria. The review results indicated that emotional regulation and self-esteem are two psychological factors that influence the resilience of unemployed mothers in exclusive breastfeeding, especially in the early postpartum period. The study's conclusions indicate that the resilience of unemployed breastfeeding mothers is significantly influenced by the balance of these two psychological factors: emotional regulation and self-esteem.Keywords: self-esteem; emotional regulation; exclusive breastfeeding; unemployed mothers ABSTRAK Air susu ibu (ASI) merupakan sumber nutrisi terbaik bagi bayi, terutama selama enam bulan pertama kehidupan. Salah satu aspek penting keberhasilan menyusui yang sering diabaikan adalah kesejahteraan psikologis ibu, khususnya regulasi emosi dan harga diri. Tujuan dari studi ini adalah memperoleh informasi mengenai regulasi emosi dan harga diri sebagai faktor psikologis yang memengaruhi resiliensi ibu dalam pemberian ASI eksklusif pada ibu yang tidak bekerja. Studi ini merupakan narrative literature review dari empat database yakni BMC Pregnancy and Childbirth, BMC Public Health, Google Scholar dan Google Scholar Indonesia hingga 6 November 2025. Keywords yang digunakan untuk database BMC adalah "emotional regulation" AND "self-esteem" AND "exclusive breastfeeding" AND "non working mother"; untuk Google Scholar adalah "maternal" AND "emotional regulation" AND "self-esteem" AND "resilience" AND "exclusive breastfeeding" AND "non working mother"; untuk Google Scholar Indonesia adalah "regulasi ibu" AND "emosi" AND "harga diri" AND "ketahanan" AND "pemberian ASI eksklusif" AND "ibu yang tidak bekerja". Sebanyak 15 artikel telah memenuhi kriteria. Hasil review menunjukkan bahwa regulasi emosi dan self esteem merupakan dua faktor psikologis yang memengaruhi ketahanan ibu yang tidak bekerja dalam pemberian ASI secara eksklusif, terutama pada periode postpartum awal. Kesimpulan studi menunjukkan bahwa ketahanan ibu menyusui yang tidak bekerja sangat dipengaruhi oleh keseimbangan dua faktor psikologis yaitu regulasi emosi dan self-esteem.Kata kunci: harga diri; regulasi emosi; air susu ibu eksklusif; ibu tidak bekerja